การเสริมสร้างความรู้ และความตระหนักในการอนุรักษ์ป่าชุมชนให้แก่เยาวชน โดยการมีส่วนร่วมระหว่างโรงเรียน บ้าน และวัด: กรณีศึกษา เยาวชนโรงเรียนบ้านโนนสมบูรณ์ เมืองบอลิคัน แขวงบอลิคำไซ สาธารณรัฐประชาธิปไตยประชาชนลาว - มมวงศ์ สุลิยา (Journal of Graduate School Sakon Nakhon Rajabhat University, 2017)
การเสริมสร้างความรู้ และความตระหนักในการอนุรักษ์ป่าชุมชนให้แก่เยาวชน โดยการมีส่วนร่วมระหว่างโรงเรียน บ้าน และวัด: กรณีศึกษา เยาวชนโรงเรียนบ้านโนนสมบูรณ์ เมืองบอลิคัน แขวงบอลิคำไซ สาธารณรัฐประชาธิปไตยประชาชนลาว Enhancing Knowledge and Awareness in Conserving the Community Forest to the Youths through Participation between the School, Village and Temple : A Case Study in Nonsomboun Village School, Bolikhan District, Bolikhamxai Province, Lao People’s Democratic Republic บทคัดย่อ การวิจัยครั้งนี้มีความมุ่งหมายเพื่อ 1) ศึกษาสภาพปัญหาในการอนุรักษ์ป่าชุมชนของประชาชนบ้านโนนสมบูรณ์ 2) สร้างกิจกรรมการเสริมสร้างความรู้ และความตระหนักในการอนุรักษ์ป่าชุมชนให้แก่เยาวชนโรงเรียน บ้านโนนสมบูรณ์ โดยการมีส่วนร่วมระหว่าง โรงเรียน บ้าน และวัด และ 3) ศึกษาผลการนำร่องทดลองใช้กิจกรรมการเสริมสร้างความรู้ และความตระหนักในการอนุรักษ์ป่าชุมชนให้แก่เยาวชนโรงเรียนบ้านโนนสมบูรณ์ โดยการมีส่วนร่วมระหว่าง โรงเรียน บ้าน และวัด กลุ่มเป้าหมายในการวิจัยครั้งนี้ ได้แก่ นักเรียนชั้นประถมปีที่ 5 ปีการศึกษา 2558 จำนวน 32 คน เครื่องมือเก็บรวบรวมข้อมูล ได้แก่ 1) แบบสัมภาษณ์บริบทชุมชน และสภาพปัญหาในการอนุรักษ์ป่าชุมชน 2) แบบทดสอบความรู้ 3) แบบทดสอบความตระหนัก 4) เอกสารประกอบการอบรม และ 5) แบบสอบถามความพึงพอใจต่อการเข้าร่วมกิจกรรมนำร่องทดลองใช้กิจกรรม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ย ร้อยละ ส่วนเบี่ยงเบนมาตรฐาน และการทดสอบทีแบบสองกลุ่มไม่อิสระกัน ผลการวิจัย พบว่า 1. สภาพปัญหาที่เกิดขึ้นกับป่าชุมชนบ้านโนนสมบูรณ์ ได้แก่ 1) การปรับเปลี่ยนคณะกรรมการปกครองหมู่บ้านบ่อยครั้งทำให้มีผลต่อการสานต่อในการคุ้มครองป่าชุมชนของหมู่บ้านไม่ต่อเนื่อ 2) คณะกรรมการคุ้มครองป่าชุมชนหมู่บ้านโนนสมบูรณ์ไม่มีการส่งเสริมคนรุ่นใหม่ คือ เด็กและเยาวชนในหมู่บ้านอย่างเป็นระบบเพื่อส่งเสริมให้เยาวชนมีส่วนร่วมในการคุ้มครองป่าชุมชน 3) ประชาชนเข้าไปลักลอบตัดไม้มีค่าเพื่อขายให้แก่โรงงานไม้ 4) ประชาชนในหมู่บ้านเข้าไปบุกรุกป่าชุมชนเพื่อการครอบครองที่ดินในพื้นที่ป่าชุมชน 5) การล่าสัตว์ป่าและหาปลาในพื้นที่ป่าชุมชนด้วยวิธีที่รุนแรง และ 6) การเก็บของป่าในป่าชุมชนไม่มีการควบคุม ดูแล ด้วยวิธีการที่เหมาะสม สาเหตุของปัญหาที่เกิดขึ้นกับป่าชุมชน พบว่า ชุมชนหมู่บ้านโนนสมบูรณ์ยังขาดความรู้ และความตระหนักในการอนุรักษ์ป่าชุมชน ประชาชนไม่เข้าใจอย่างลึกชึ้งต่อคุณประโยชน์ และคุณค่าของป่าชุมชน รวมทั้งยังไม่มีการสร้างกิจกรรมส่งเสริมให้เด็กเยาวชนคนรุ่นใหม่เข้ามามีบทบาทร่วมด้วยช่วยกันในการอนุรักษ์ป่าชุมชน และเพื่อเป็นการสร้างจิตสำนึกให้เยาวชนรู้รัก และหวงแหนป่าชุมชนบ้านโนนสมบูรณ์ให้มีความอุดมสมบูรณ์อย่างยั่งยืน 2. กิจกรรมการเสริมสร้างความรู้ และความตระหนักในการอนุรักษ์ป่าชุมชนให้แก่เยาวชนโรงเรียนบ้านโนนสมบูรณ์โดยการมีส่วนร่วมระหว่างโรงเรียน บ้าน และวัด ประกอบด้วย 4 กิจกรรม ได้แก่ 1) กิจกรรมการอบรมเสริมสร้างความรู้และความตระหนักในการอนุรักษ์ป่าชุมชนให้แก่เยาวชนโรงเรียนบ้านโนนสมบูรณ์ 2) กิจกรรมค่ายเยาวชนเดินป่าชุมชนบ้านโนนสมบูรณ์ 3) กิจกรรมปลูกต้นไม้เสริมป่าชุมชนบ้านโนนสมบูรณ์ และ 4) กิจกรรมบวชต้นไม้ในป่าชุมชนบ้านโนนสมบูรณ์ 3. หลังการนำร่องทดลองใช้กิจกรรม เยาวชนโรงเรียนบ้านโนนสมบูรณ์ มีความรู้ และความตระหนักในการอนุรักษ์ป่าชุมชน สูงกว่าก่อนการนำร่องทดลองใช้กิจกรรมอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 และผ่านเกณฑ์ที่กำหนด โดยมีความพึงพอใจต่อการเข้าร่วมกิจกรรมต่างๆ อยู่ในระดับมาก Abstract The purposes of this study were: 1) to investigate the problem state of conserving the Community Forest of the people in Nonsomboun village, 2) to create activities to enhance knowledge and awareness of conserving the Community Forest to the youths in Nonsomboun Village School through participation between the school, village and temple and 3) to examine the result of activities implementation to enhance knowledge and awareness of conserving the Community Forest to the youths in Nonsomboun Viiage School through participation between the school, village and temple. A sample of this study was 32 grade-5 students in academic year 2015. The instruments for collecting data were: 1) an interview guide of community context and problem state in conserving the Community Forest, 2) a test of knowledge, 3) a test of awareness 4) a handout supplement paper and 5) a questionnaire of satisfaction with participation in the pilot experiment of using the activities. Statistics used to analyze data were mean, percentage, standard deviation and t-test for dependent samples. The findings of study disclosed as follows: 1. The problems incurred with the Nonsomboun village community forest were: 1) Frequent modifications of the village governing committee resulted in the lack of continuing protection of the Community Forest; 2) the Nonsomboun village community forest protection committee did not have a system in promoting the young new generation to participate in protection of the Community Forest; 3) some people had illegal logging for sale to the wood factory; 4) some people in the village invaded the Community Forest for occupying the land, 5) hunting wild animals and fishing in the Community Forest area by the violent methods; 6) lack of proper caring and controlling those who collected the Community Forest products. The causes of the problem with the Community Forest were found that people in the Nonsomboun village community lacked knowledge and awareness of conserving the Community Forest. The people did not fully understand the benefits and value of the Community Forest. The youths were not provided with activities for enhancing them as a new generation to be involved in conserving the Community Forest through creating their awareness of love with the Nonsomboun community forest and of being ready to protect and conserve it for its sustainability and productiveness. 2. The activities to enhance knowledge and awareness in conserving the Nonsomboun community forest to the youths through participation between the school, village and temple consisted of 4 activities: 1) activity of training the youths in Nonsomboun Village School for strengthening knowledge and awareness in conserving the Community Forest, 2) youths’ camp activity for hiking in the Nonsomboun village community forest, 3) activity of planting trees for enhancing the Nonsomboun village community forest, and 4) activity of ordaining trees in the Nonsomboun village community forest. 3. After the pilot experiment of using the Activities, the youths of Nonsomboun Village School had significantly higher knowledge and awareness of conserving the Community Forest than those before the treatment at the .01 level; and it passed the prescribed criterion. All the youths were satisfied with participation in the different activities at high level.